Chapter 9 Not Just the Science A Transdisciplinary Pedagogy for Cryospheric Climes - Singh, Vandana (Taylor & Francis, 2023)
This chapter presents a transdisciplinary, justice-centered pedagogy for cryospheric climes, examining and developing the notion of a clime through a focus on the Alaskan Arctic and the diminishing sea ice. Through stories from the Arctic region and a scientific invocation of sea ice, I argue for the usefulness of a teaching approach where the climate itself becomes teacher, allowing a for natural entanglement of the scientific and the social. Through this radical reorientation, certain key lessons emerge when we listen to the sea ice. These emerge as three interconnected meta-concepts that, along with justice, form the framework of this pedagogy. I explore how these meta-concepts transcend apparent dichotomies of clime and climate, local and global, Indigenous and mainstream, as well as scientific and social. Stories play a key role in facilitating this travel across boundaries. I illustrate this with stories that begin in the human realm and allow us to travel to the scientific, as well as stories that begin with science and reach toward the human. By considering clime as an enactment with multiple players-humans, non-human animals, and elements of weather and landscape-a more-than-human understanding of the climate problem becomes possible.